Strengthening the Community-Based Implementation System to Support Education for Children from Low-Income Families in Sukaresmi District - Nur Lathifah; Dede Kuswanda; Milly Mildawaty (International Journal of Social Sciences and Humanities, 2026)
Poverty in Sukaresmi District, Cianjur Regency, increases the risk of school dropout among children from low-income families. Although the sponsorship programme implemented by Yayasan Usaha Mulia (YUM) supports children’s educational continuity, limited parental involvement and weak collaboration with local resource systems remain key challenges. This study aimed to develop a community-based implementation system strengthening design through the Sponsorship Parents Community to support children’s education. Using a Participatory Action Research (PAR) approach, the study involved reflection, needs assessment, planning, implementation, evaluation, and final design development. Data were collected through focus group discussions, in-depth interviews, participant observation, and document analysis involving community members and local resource actors. The findings show that strengthening actors, resources, structures, and procedures improved community organisation, capacity building, and collaboration among Sponsorship Project Officers, SIKS-NG operators, PIP operators, PSM, and TKSK. By 14 April 2026, 26 households had been registered in DTSEN, 17 households were recorded as PIP beneficiaries, and only one household remained unregistered. The study concludes that community empowerment and social network-based implementation can improve community functioning and educational access for low-income families.